Qualidade de vida dos estudantes de mestrado da Universidade Federal de Mato Grosso - UFMT - Oliveira Junior, Gilmar Jorge de (2020)
The master's course may require from the student several adaptations in his life, which end up interfering positively or negatively in his quality of life, since it varies with the moment and circumstances experienced individually or collectively. Objective: To evaluate the quality of life and its associated factors in master's students at the Federal University of Mato Grosso in 2018. Method: This is an observational, cross-sectional study, of the self-filling survey type, with the collection of data being carried out online, in a sample of 375 master's students, 306 students and 69 professionals, who answered the instruments Epworth Sleepiness Scale, SRQ-20 and WHOQOL-bref, in addition to questions related to sociodemographic, academic, style of life and health status. The sample had its description by means of tables, graphs, position and dispersion measures, in addition, it used statistical inference techniques such as interval estimates, hypothesis tests and the multiple Poisson regression model with robust variance to verify the associations. Results: Comparing the 95% confidence intervals, there was no significant difference between the general quality of life of academic and professional master's students, when analyzing them together, a 95% confidence interval was obtained for the mean score of [55.4; 58.2]. The variables marital status, length of course, advisor, availability for the course, common mental disorders and physical activity showed a significant association with the general quality of life. The negative perception of quality of life and health was significantly associated with lower scores in the psychological domain, with a prevalence ratio (RP) of 7.27, while the positive perception was significantly associated with higher scores in the physical domain [RP = 2.36], psychological [RP = 1.57] and the environment [RP = 1.63]. Conclusion: The quality of life of master's students was classified as median, but less than 31% of them had a positive perception when analyzing it together with their health, indicating the need to reflect on the importance of operationalizing prevention and recovery actions grievances, so that they are strengthened mentally, physically and emotionally, thus increasing their capacity to fully respond to the challenges faced in this phase.